The Influence Of Service Quality On Consumer Satisfaction At Truntum Hotel Padang - Zengga, Zengga; Rifdatul Husna; Rafidola Mareta Riesa (Jurnal Ekonomi, 2024)
The purpose of this research is to determine the influence of service quality on consumer satisfaction at the Truntum Padang Hotel. This research method is quantitative descriptive, with the variables Service Quality and Consumer Satisfaction. The population in this study were guests who had stayed at the Truntum Padang Hotel in the period November 2022 to April 2023. The sampling technique used the incidental sampling method, that is, anyone who happened to meet the researcher could be used as a sample with a suitable category as a data source. The number of samples in this research was 100 respondents. The data collection technique uses a questionnaire with an interval scale whose validity and reliability have been tested. Next, analyze the data using SPSS.